The analgesic effect of dexketoprofen trometamol when added to lidocaine for intravenous regional anesthesia (Annals of Medical Research, 2021)
Aim: The purpose of this study was to evaluate the duration of onset and regression time of sensory and motor blocks, tourniquet pain, and postoperative analgesia with the addition of dexketoprofen trometamol to lidocaine solution in intravenous regional anesthesia (IVRA) for hand surgery. Material and Methods: This study was designed as a retrospective analysis. Records, including perioperative anesthesia notes, of 290 patients evaluated and 75 identified as eligible that underwent IVRA with an upper extremity Bier block and a corresponding tourniquet time of less than 1 hour were reviewed. Patients undergoing IVRA with lidocaine (3 mg/kg) were compared with those receiving dexketoprofen trometamol (50 mg) as an adjuvant in IVRA (the D-IVRA group) or as intravenous analgesia in the non-operated arm (the D-IV group) . All hemodynamic values, sensorial/motor block onset and regression times, VAS values, intraoperative and postoperative analgesic requirements, and all complications were recorded. Results: Sensory block onset time was shorter and motor block regression time longer in the D-IVRA group. After tourniquet deflation, all perioperative VAS scores in the D-IVRA group were lower than those of the control group. VAS scores were lower in the D-IVRA group compared to the D-IV group, especially at 30 min and 1 h postoperatively.Conclusion: The addition of dexketoprofen trometamol to lidocaine in IVRA may increase the quality of anesthesia and analgesia in hand surgery.
Keywords: Dexketoprofen trometamol; lidocaine; IVRA; local anesthetics; NSAIDs